Retrofit ‘daemons’ in the process of low-carbon housing stock renovation - Topouzi, M; Killip, G; Owen, A (European Council for an Energy Efficient Economy, 2017)
The ‘performance gap’ between design and actual energy use is well recognised. Much of the debate on the performance gap focuses on the use and accuracy of building energy models or on users' ‘misbehaviour’ and measures' maloperation. This paper focuses instead on the design and construction phases of retrofit projects.